A model for optimizing the structure of teaching techniques for distance learning in the Russian higher education system - Zhanna Gardanova; Vadim V. Ponkratov; N. V. Kuznetsov; Natalya Nikitina; Olesya Dudnik; Endzhe Latypova; Sergey Shcherbatykh (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study aims to develop a methodical approach to optimize the structure of teaching techniques and approaches to distance education, as exemplified by Russian universities, to enhance students' professional competencies. A pedagogical experiment was conducted with the participation of 746 second to fourth year students majoring in engineering at the Ural Federal University in Russia. The coefficients for the relative importance of professional competencies were obtained through expert assessment. The number of experts was 40 faculty members with teaching experience of more than five years. The pedagogical experiment revealed the regularities of the influence of the forms of distance learning on the formation of students' professional competency levels. The values of students' developmental competency levels have been determined. Non-linear regression models have been developed based on the values of the integral level of professional competencies and the percentage of distance-learning forms in the number of instructional hours. The proposed methodological approach will be useful for university professors and teachers in identifying the most effective forms of distance learning and in differentiating teaching methods not only in the context of the general pandemic but also in the natural conditions of the educational process.
Keywords: 650; COVID-19; distance learning; higher education; pandemic; professional competencies; students